EXPLORING UNDERGRADUATE STUDENTS’ VIEW ON THE IMPLEMENTATION OF A FIELDWORK ACTIVITY - Pratiwi, Andi Citra; Syawal, Muhammad Khamzah; Mar’ah, Zakiyah; Arsyad, Susalti Nur (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2024)
Fieldwork is crucial in biological education, particularly in zoology, as it offers students practical and experiential learning that deepens their understanding of biological concepts. In the context of invertebrate zoology, fieldwork exposes students to the diversity, behavior, and ecology of invertebrates in their natural environments, thereby enhancing theoretical knowledge and developing essential skills like observation, data collection, and scientific analysis. This descriptive quantitative study explores undergraduate students' perspectives on fieldwork in a Zoology Invertebrate course. Conducted in May 2023, the research involved 32 students enrolled in the course, selected for their relevant experience in fieldwork. Data was gathered using a structured questionnaire which utilized a 5-point Likert scale, focusing on two main themes: students' preference for joining fieldwork and the perceived educational benefits of fieldwork. The questionnaire, administered online immediately after the fieldwork, ensured fresh and accurate responses. Results indicate a strong preference for fieldwork as a learning method and a positive impact on students' understanding of invertebrate zoology concepts. This study underscores the importance of fieldwork in biological education, highlighting its role in enhancing student engagement and comprehension